Review: Influences of Semiconductor Metal Oxide Properties on Gas Sensing Characteristics - Saruhan, Bilge; Lontio Fomekong, Roussin; Nahirniak, Svitlana (Frontiers in Sensors, 2021)
Semiconductor metal oxides are widely used in gas sensors due to their excellent sensing properties, abundance and ease of manufacture. The best examples of these sensing materials are SnO2 and TiO2 that have wide bandgap and offer unique set of functional properties, the most of which are electrical conductivity and high surface reactivity. There has been a constant development of semiconductor metal oxide sensor materials in the literature that has been accompanied by the improvement of their gas-sensitive properties for gas detection. This review is dedicated to compiling these efforts in order to mark the achievements in this area. The main material specific aspects that strongly affect the gas sensing properties and can be controlled by synthesis method are morphology/nano-structuring and dopants to vary crystallographic structure of metal oxide sensing material.